PENGARUH EDUKASI KESEHATAN TERHADAP PENCEGAHAN PENULARAN COVID-19 PADA MASYARAKAT DI KELURAHAN PAYAH PASIR TAHUN 2022 - Putra Ritonga, Edisyah; Manurung, Sarida Surya; Damanik, Hamonangan; Silaban, Nataria Yanti; Naibaho, Eka Nugraha V (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Corona Virus Disease 2019 (COVID-19) is a disease caused by a new type of Coronavirus, namely Sars-CoV-2, which was first reported in Wuhan, China on December 31 2019. The North Sumatra Health Service stated that in North Sumatra on March 30 2021 There were 406 positive COVID-19 cases, 41 cases died and 122 patients recovered a day. The Medan City Health Service in general data related to COVID-19 in Medan City recorded that 14,440 people had been exposed to COVID-19, 13,019 had recovered, and 461 patients had died. This shows that Medan is a city with a COVID-19 red zone. This research aims to determine the effect of health education on preventing the transmission of COVID-19 in the community. This type is quantitative with the research design used in this research being a quasi-experimental study with a one group pretest and posttest design method. The sample size was 108 respondents. Data were collected using a questionnaire and analyzed using the Paired t test. Data were analyzed using the Paired t Test. The research results show that there is an influence of health education on preventing the transmission of COVID-19 (P = 0.00 < 0.05). Based on the research results, it can be concluded that health education plays an important role in public knowledge to prevent the transmission of COVID-19. It is hoped that all respondents and the public will continue to prevent transmission by complying with established health protocols and health workers are expected to provide information on an ongoing basis to increase public knowledge about COVID-19.